Teorias comportamentais: fatores psicológicos que influenciam a intenção em reduzir o uso do automóvel - Habiro, André (2021)
The number of private cars and their increasingly constant use are pointed out by different studies as responsible for the increase in the levels of air and noise pollution, emission of harmful gases, congestion and other effects that directly affect the quality of life of the population. Through diversified actions, governments and public managers seek to encourage the use of alternative means of transportation to reduce the impacts caused by automobiles. It is understood that the choice for a given mean of locomotion depends on several factors, but in general, an individual analysis of each situation occurs predominantly. The theory of planned behavior and the norm activation model are cited in several studies related to the theme due to the degree of efficiency of both, in understanding and predicting behaviors. The main objective of this study is to compare the adherence of the variables of each theory to the factors that influence the decisions of use and / or reduction of automobiles. Data will be obtained through an online questionnaire considering a sample of convenience and the quantitative analysis of these data will use the technique of Structural Equation Modeling (SEM) that uses several statistical techniques combined in it analyses. It is expected that with the analysis of the results obtained, it will be possible to identify the most relevant factors in the process of choosing the daily commute modal. Such information may help government officials and public administrators to draw up plans for urban displacement that consider the psychological aspects that encourage the use of alternative means of transportation to the detriment of the use of the car.